ENHANCING SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP THROUGH IMPROVED TAX ADMINISTRATION: A COMPREHENSIVE ANALYSIS (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
This scientific article delves into the pivotal role of tax administration in fostering the growth and sustainability of small businesses and private entrepreneurship. Recognizing the importance of a well-structured and efficient tax system, the paper explores various aspects of tax administration that significantly impact the functioning of small businesses. Through a thorough examination of global case studies, legislative frameworks, and empirical evidence, this article aims to provide insights into potential strategies for optimizing tax administration to benefit small businesses and private entrepreneurship.